Običajni in eksotični hadroni - Prelovšek, Saša (Obzornik za matematiko in fiziko, 2016)
Conventional hadrons are baryons ?$(qqq)$? and mesons ?$(q\bar{q})$?. Experiments have recently found candidates for exotic tetraquarks ?$(\bar{q}q\bar{q}q)$? and pentaquarks ?$(qqqq\bar{q})$?. This article sheds light on what is known about the conventional and the exotic hadrons based on the fundamental theory of strong interactions { Quantum ChromoDynamics (QCD). This is not a simple problem, since the strong force in hadrons does not allow the perturbative theoretical treatment.
Keywords: eksotični hadroni; elementary particle physics; exotic hadrons; fizika osnovnih delcev; hadroni; hadrons; kvantna kromodinamika na mreži; lattice QCD; močne interakcije; strong interactions